Effects of fertilization on litter decomposition dynamics and nutrient release in orchard systems - Nie, Huayue; You, Chunhe; Gao, Jixi (Frontiers in Plant Science, 2024)
Plant litter decomposition is a significant ecosystem function that regulates nutrient cycling, soil fertility, and biomass production. It is heavily regulated by nutrient intake. The effects of exogenous nutrients on litter decomposition are not yet fully understood. To determine how Eriobotrya japonica litter decomposition responds to adding nutrients, we used the decomposition litter bag method in the laboratory for 180 days.There were five different nutrient treatment levels used: control (no addition), low nitrogen addition (LN; 100 kg N•ha -1 • year -1 ), high nitrogen addition (HN; 200 kg N•ha -1 •year -1 ), phosphorous addition (P; 50 kg P•ha -1 • year -1 ), and micronutrients addition (M; 50 kg M•ha -1 •year -1 ).According to a repeated measures analysis of variance, adding N decreased the remaining mass (P < 0.01), reduced by 4.1% compared to the CK group.Whereas adding M increased the remaining mass (P < 0.01), increased by 6.8% compared to the CK group. Adding P had no significant effect on remaining mass. Although the amount of residual carbon (C) was unaffected, adding N increased the level of residual N in the litter. Litter C content, K content, N concentration, and C/N ratio were linearly correlated to litter remaining (P < 0.01). Although adding nutrients decreased soil enzyme activity later in the decomposition process, no significant correlation was detected between enzyme activity and the remaining. N fertilization treatments decreased the soil microbial diversity index. The addition of nitrogen and micronutrients reduced the abundance of Acidobacteria, while HN addition increased the abundance of Actinobacteria. The addition of micronutrients increased the abundance of Proteobacteria. These results imply that N-induced alterations in the element content of the litter regulated the effects of nutrient inputs on litter decomposition. This study can be a reference for the fertilization-induced decomposition of agricultural waste litter.